Cryptocurrencies and capital flows: Evidence from El Salvador's adoption of Bitcoin - Stefan Goldbach; Volker Nitsch (Technische Universität Darmstadt, Department of Law and Economics, 2024)
This paper explores a monetary experiment, the adoption of Bitcoin as legal tender in El Salvador in 2021, to analyze the impact of digital currencies on international capital flows. Using a difference-in-differences approach, we find that, instead of making transfers easier, El Salvador's official cross-border financial activity has decreased after the monetary change. This finding may reflect an increase in uncertainty. However, it is also in line with findings that link digital assets to illegal activity as previously officially recorded financial transfers may have been replaced by unrecorded activities.
urn:nbn:de:tuda-tuprints-280169
Keywords: E42; E58; F21; F32; F38; 330; crypto-assets; digital currency; legal tender; bitcoin